The Influence of Leadership Style, Teamwork and Communication on Work Productivity (Case Study at PT. BFI Finance Indonesia, BFI Tower) - desi lusriani Ubaidah; Masruri Masruri; Eko Trianto (PT. Anagata Sembagi Education, 2025)
This study aims to determine and analyze the influence of leadership style, teamwork, and communication on employee work productivity at PT. BFI Finance Indonesia. The problem raised in this study is related to the variables of leadership style, teamwork, and communication that have not been running efficiently, which is thought to have an impact on employee work productivity. This study uses a quantitative approach with a survey method through the distribution of questionnaires. The population in this study were employees of PT. BFI Finance Indonesia who are at BFI Tower, with a sample of 77 respondents determined using the Taro Yamane formula. Instrument testing was carried out through validity and reliability tests, and data analysis using the SmartPLS 4 application. Hypothesis testing in this study was carried out through path coefficient analysis. The results of the study showed that leadership style has a positive and significant effect on work productivity. This is indicated by the original sample value of 0.467 and t-statistic of 3.285 and p-values of 0.001. Teamwork does not have a significant effect on work productivity. This is indicated by the original sample value of 0.055, a t-statistic of 0.343, and a p-value of 0.732. Communication has a positive and significant effect on work productivity, as indicated by the original sample value of 0.271, a t-statistic of 2.069, and a p-value of 0.039